Low-carbon high-performance concrete and preparation method thereof
By using the synergistic effect of components such as silicate cement, sulfoaluminate cement and other components in concrete, combined with the efficient preparation method of activated coal gangue powder and modified basalt fibers, the problems of high carbon emissions and insufficient performance of concrete are solved, and the problem of low carbon emissions and performance of concrete is achieved. The development of low-carbon and high-performance concrete has good economic and environmental benefits.
Patent Information
- Application Number
- CN202411307064.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-07
AI Technical Summary
Existing concrete is highly carbon emissions during the production process and it is difficult to simultaneously reduce costs and improve mechanical properties and crack resistance.
Adopt low-carbon high-performance concrete formulas, including silicate cement, sulfur aluminate cement, activated gangue powder, fly ash, modified basalt fiber, limestone powder, lightly burned magnesium oxide, modified polycarboxylic acid water reducer and water, through the synergistic action of each component, the strength, durability and crack resistance of concrete are improved, and the performance of activated gangue powder and modified basalt fibers are improved through mechanical activation and thermal activation processes.
It significantly reduces carbon emissions, improves the compressive strength, crack resistance and durability of concrete, is suitable for large-scale promotion and application, and at the same time reduces production costs.
Smart Images

Figure BDA0005049547660000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building construction materials, and in particular to a low-carbon high-performance concrete and a preparation method thereof. Background Art
[0002] The engineering construction industry accounts for more than 40% of global carbon emissions. As the most widely used building material, concrete accounts for 6-10% of global carbon emissions. In the context of countries around the world actively "reducing carbon emissions", the development and utilization of low-carbon concrete has very important practical significance. Cement is the main source of carbon emissions from concrete. For every ton of Portland cement clinker produced, about 830kg of CO2 is emitted. Therefore, how to reduce carbon emissions while reducing costs and improving the mechanical properties and crack resistance of concrete has become an urgent problem to be solved. Summary of the invention
[0003] The purpose of this application is to provide a low-carbon, high-performance concrete and a preparation method thereof in response to the deficiencies of current technology. The low-carbon, high-performance concrete prepared in this application has the advantages of simple preparation, low cost, and green environmental protection. It also has good compressive strength, slump, expansion, setting time, crack resistance and durability. In addition, it also has significant economic and environmental benefits, greatly reduces carbon emissions, and is suitable for large-scale promotion and application.
[0004] In the first aspect, the present application provides a low-carbon high-performance concrete, which adopts the following technical solution: A low-carbon high-performance concrete comprises the following raw materials, measured by weight: 150-180 parts of silicate cement, 24-27 parts of sulphoaluminate cement, 120-150 parts of activated coal gangue powder, 60-80 parts of fly ash, 600-700 parts of sand and gravel, 60-65 parts of modified basalt fiber, 20-25 parts of limestone powder, 10-12 parts of light-burned magnesium oxide, 2-3 parts of accelerator, 7-10 parts of modified polycarboxylic acid water reducer and 180-220 parts of water.
[0005] By adopting the above technical solution, in the low-carbon high-performance concrete of this application, each component plays a unique role and has a synergistic effect with each other to jointly improve the performance of concrete. Portland cement provides basic bonding and strength, while sulfoaluminate cement generates calcium sulfonate and aluminum hydroxide through its rapid hydration reaction to form a skeleton and improve early strength. The combination of the two not only ensures the long-term stability and strength of the concrete, but also achieves the requirements of early high strength. Activated coal gangue powder, after activation treatment, improves the activity of volcanic ash, and its internal [SiO4 4- ] and [AlO2 -] groups react with Ca(OH)2 to generate hydrated calcium silicate and hydrated calcium aluminate, which enhances the strength. It reacts with Ca(OH)2, the reaction product of silicate cement and sulphoaluminate cement, to reduce its concentration, promote further hydration of cement, and continuously improve the strength of concrete. Fly ash, as a filling material, improves the workability and density of concrete, while participating in the hydration reaction and contributing additional strength. It works together with activated coal gangue powder to improve the overall density and crack resistance of concrete. Sand and gravel provide the basic skeleton of concrete, ensuring the volume stability and durability of concrete. It works together with other components to ensure that concrete has good mechanical properties and durability. Modified basalt fiber provides tensile stress at high temperature, resists thermal expansion, and improves the high temperature crack resistance of concrete. It works together with lightly burned magnesium oxide to enhance the stability and durability of concrete in high temperature environments. Limestone powder, as a fine filler, improves the interface transition zone of concrete and improves compressive strength and durability. It works together with modified polycarboxylate water reducer to optimize the pore structure of concrete and improve crack resistance. Lightly burned magnesium oxide participates in the hydration reaction to generate hydration products with cementing effect, which improves the strength and durability of concrete. Together with modified basalt fiber, it improves the crack resistance of concrete at high temperature. The accelerator accelerates the cement hydration reaction, reduces the amount of cement, and improves the early strength and durability of concrete. Together with silicate cement and sulphoaluminate cement, it achieves early high strength and good durability of concrete. Modified polycarboxylate water reducer provides excellent dispersibility, improves the pore structure of concrete, and improves compressive strength and crack resistance. Together with limestone powder, it optimizes the microstructure of concrete and improves the overall performance. Water is used as a reaction medium to ensure that all components can fully react to form a uniform and dense concrete structure. In summary, the low-carbon high-performance concrete in this application achieves the goals of high strength, high durability, low carbon emissions and good workability through the individual effects of each component and their synergistic effects, providing an environmentally friendly and excellent material selection for construction projects.
[0006] Preferably, the preparation method of the activated coal gangue powder is: first use a jaw crusher to crush the blocky coal gangue into particles with a particle size of 6-10 mm, put the crushed coal gangue particles into a ball mill, use a steel ball with a diameter of 20 mm, a ball-to-material ratio of 4:1, and ball mill for 120 minutes at a speed of 100 r / min to obtain coal gangue powder, and sieve the coal gangue powder through a 150-mesh sieve to obtain ball-milled activated coal gangue powder; then put the ball-milled activated coal gangue powder into a high-temperature furnace at 750°C, keep it warm for 45 minutes for thermal activation, and after the thermal activation is completed, immediately take the coal gangue powder out of the high-temperature furnace and naturally cool it to room temperature at room temperature to obtain activated coal gangue powder.
[0007] By adopting the above technical scheme, the preparation method of activated coal gangue powder involves two main steps: mechanical activation and thermal activation. These two steps work together to enhance the volcanic ash activity of coal gangue powder, allowing it to play a greater role in concrete. Mechanical activation: The blocky coal gangue is crushed into particles with a particle size of 6-10mm by a jaw crusher, and then finely ground using a ball mill to increase the specific surface area of the coal gangue powder and make the particle size distribution more uniform. During the mechanical activation process, the crystal structure of the coal gangue is destroyed, and its internal [SiO4 4- ] and [AlO2 - ] groups react with Ca(OH)2, thereby increasing its volcanic ash activity. Thermal activation: The ball-milled gangue powder is placed in a high-temperature furnace at 750°C for 45 minutes. The chemical and mineral composition of the gangue is changed by high-temperature treatment to further increase its activity. During the thermal activation process, the minerals in the gangue change to produce more reactive components, which react with cement hydration products to accelerate the formation of strength. As the gangue reacts with Ca(OH)2, the concentration of Ca(OH)2 in the cement paste decreases, which promotes the further hydration of C3S and C2S in Portland cement. As an admixture for concrete, the activated gangue powder reacts with Ca(OH)2 in the hydration products of Portland cement and sulphoaluminate cement to produce hydrated calcium silicate and hydrated calcium aluminate, thereby enhancing the strength of concrete. Activated coal gangue powder not only improves the early and long-term strength of concrete, but also reduces carbon emissions and achieves environmental benefits by replacing part of the cement and reducing the amount of cement used. At the same time, the increase in its activity helps to improve the strength of concrete throughout its entire age, ensuring the durability and long-term performance of concrete. In summary, the preparation method of activated coal gangue powder effectively improves the volcanic ash activity of coal gangue through two steps of mechanical activation and thermal activation, so that it plays a key role in low-carbon high-performance concrete, which not only improves the strength and durability of concrete, but also achieves a dual improvement in environmental and economic benefits.
[0008] Preferably, the method for preparing the modified basalt fiber comprises the following steps: S31. According to the mass fraction, 10 parts of basalt fiber and 7 parts of spodumene were put into a ball mill and ground for 5-6 hours, then heated to 260°C at a rate of 4°C / min, kept warm for 9 hours, then heated to 460°C at a rate of 5°C / min and kept warm for 8 hours, and finally heated to 670°C at a rate of 6°C / min and kept warm for 2 hours, and then cooled in the furnace to obtain a mixed powder; S32. According to the mass proportions, 10 parts of the mixed powder were mixed evenly with 12 parts of high-rubber powder, 12 parts of calcium carbonate powder, 6 parts of compatibilizer and 4 parts of titanium dioxide. Under the protection of nitrogen atmosphere, the mixture was heated to 1700°C for melt blending for 1.6 hours. Then, a twin-screw extruder was used to extrude the roving at a speed of 150 rpm / min. The roving was then connected to a wire drawing machine. The temperature in the wire drawing machine was controlled at 750°C and the speed of the wire drawing machine was controlled at 300 m / min to obtain filaments with a diameter of 10-20 μm. Finally, the filaments were cut into a length of 15 mm by a cutting machine to obtain modified basalt fibers.
[0009] By adopting the above technical scheme, the preparation method of modified basalt fiber involves multiple steps, including grinding, heat treatment, melt blending, extrusion and drawing, etc. These steps work together to improve the performance of basalt fiber and make it play a greater role in concrete. Step S31: Through ball milling and segmented high temperature treatment, the mixing uniformity of basalt fiber and spodumene is improved, the chemical reaction between the two is promoted, and a new mineral phase is formed. High temperature treatment helps to improve the chemical stability and mechanical strength of the mixture, laying the foundation for the subsequent melt blending and drawing process. Step S32: Through melt blending and extrusion drawing, the physical and chemical properties of the fiber are further improved, so that it has better temperature resistance and mechanical properties. The addition of high glue powder and calcium carbonate powder improves the adhesion and processability of the mixture, while the addition of compatibilizer and titanium dioxide improves the compatibility and dispersibility of the fiber with other concrete components. After the modified basalt fiber is added to the concrete, tensile stress is generated at high temperature, which resists the thermal expansion of the concrete, maintains the volume thermal stability, and improves the crack resistance. Modified basalt fiber works together with other components such as sulphoaluminate cement and modified polycarboxylate water reducer to achieve high performance and long-term stability of concrete by improving its early strength and crack resistance. In summary, the preparation method of modified basalt fiber effectively improves the performance of the fiber through a series of physical and chemical treatments, making it play a key role in low-carbon high-performance concrete, not only improving the crack resistance of concrete, but also enhancing the overall performance and durability of concrete through its synergistic effect with other components.
[0010] Preferably, the compatibilizer is maleic anhydride grafted polypropylene, and the grafting rate is 1%.
[0011] Preferably, the preparation method of the modified polycarboxylate water-reducing agent comprises the following steps: S51. Add 18 mol of acrylic acid and 1 mol of methyltrimethoxysilane to 5 kg of water, stir evenly, and obtain a mixed solution A; S52. Add 0.3 mol of vitamin C and 0.8 mol of 3-mercaptopropionic acid to 2 kg of water, stir evenly, and obtain a mixed solution B; S53. Add 1 mol of benzoic anhydride-modified methyl allyl polyoxyethylene ether and 7 mol of isopentanol polyoxyethylene ether to 23 kg of water and stir, then add 1 mol of hydrogen peroxide, stir and heat to 47°C, then add dropwise the mixed solution A and the mixed solution B at the same time, after the addition is completed for 3 hours, continue stirring and react for 3 hours, then add NaOH aqueous solution to adjust the pH value to 6.8, and obtain a modified polycarboxylic acid water reducer.
[0012] By adopting the above technical scheme, the preparation method of the modified polycarboxylic acid water reducer involves multiple chemical reaction steps, which work together to generate a water reducer with special structure and performance, thereby playing a key role in concrete. Step S51: By mixing acrylic acid and methyltrimethoxysilane, a mixture containing silicone and carboxylic acid groups is initially formed, laying the foundation for subsequent reactions. The mixture in this step can provide the functional groups required for subsequent reactions to ensure that the final product has the required structure and performance. Step S52: The mixed solution B of vitamin C and 3-mercaptopropionic acid provides a reducing agent and a chain transfer agent for the subsequent polymerization reaction, which helps to control the molecular weight and structure of the polymer. The addition of the chain transfer agent helps to adjust the molecular weight distribution of the polymer, thereby affecting the performance of the water reducer, such as dispersibility and adsorption capacity for cement particles. Step S53: A free radical copolymerization reaction is carried out in the aqueous phase, and the polyether macromonomer modified by benzoic anhydride is polymerized with acrylic acid and silane compounds to form a polymer with a specific structure. The addition of hydrogen peroxide initiates free radical polymerization, and the temperature control is to ensure the smooth progress of the reaction. In this step, the precise control of the molar ratio of each reactant and the reaction conditions (such as temperature and time) is crucial to the generation of a water reducer with excellent performance. The pH value is adjusted to 6.8 to ensure the stability and performance of the product. The modified polycarboxylate water reducer effectively improves the pore structure of concrete and improves the compressive strength and crack resistance of concrete through its steric hindrance effect and dispersion performance. Working together with components such as activated coal gangue powder and sulphoaluminate cement, the modified polycarboxylate water reducer not only improves the workability of concrete, but also promotes the early and long-term strength development of concrete, while reducing the amount of cement and reducing carbon emissions. In summary, the preparation method of the modified polycarboxylate water reducer generates a water reducer with excellent performance through a precisely controlled chemical reaction. Its application in low-carbon high-performance concrete not only improves the comprehensive performance of concrete, but also achieves economic and environmental benefits.
[0013] Preferably, the accelerator comprises the following raw materials, calculated by weight: 100 parts of hydroxyethyl acrylate, 0.2 parts of dicumyl peroxide, 9 parts of bis(allyl alcohol)-terminated polyoxyethylene ether, 5 parts of triisopropanolamine, 4 parts of 1-amino-2-methyl-2-propanol, 110 parts of acetone, and 100 parts of water.
[0014] By adopting the above technical scheme, the preparation method of the accelerator involves the mixing and reaction of multiple components, which work together to form an accelerator with specific functions, which plays a key role in concrete. Hydroxyethyl acrylate: As a polymerization monomer, it provides the basic skeleton of the polymer. Diisopropylbenzene peroxide: As an initiator of free radical polymerization, it promotes the polymerization reaction. Diallyl alcohol-terminated polyoxyethylene ether: As a cross-linking agent, it participates in the polymerization reaction, increases the molecular weight and network structure of the polymer, thereby improving the crack resistance and durability of the concrete. Triisopropanolamine: As a catalyst, it accelerates the polymerization reaction, and may also participate in the formation of the network structure, thereby improving the early strength of the concrete. 1-Amino-2-methyl-2-propanol: Contains amino groups, can absorb carbon dioxide in the air, undergo carbonization reaction, and improve the early strength of concrete. Acetone and water: As solvents, they ensure the uniformity of the reaction and facilitate the mixing of the accelerator with other concrete components. Synergistic effect between bis-allyl alcohol-terminated polyoxyethylene ether, triisopropanolamine, and 1-amino-2-methyl-2-propanol: These components interact with each other in the polymerization reaction to form a polymer network with specific structure and properties. As a crosslinker, bis-allyl alcohol-terminated polyoxyethylene ether reacts with hydroxyethyl acrylate to form a network structure; triisopropanolamine acts as a catalyst to accelerate this process; and 1-amino-2-methyl-2-propanol improves the early strength of concrete through the carbonization reaction of its amino group. The combined effect of these components not only improves the early strength of concrete, but also improves its crack resistance and durability. Through the interaction of the above components, the accelerator effectively reduces the amount of cement in concrete, while improving the strength, crack resistance and durability of concrete materials. The addition of this accelerator enables low-carbon high-performance concrete to achieve higher early strength and better environmental adaptability while maintaining good workability, providing strong support for the large-scale application of concrete.
[0015] Preferably, the preparation method of the accelerator is: according to the mass parts, hydroxyethyl acrylate, diisopropylbenzene peroxide, bis(allyl alcohol)-terminated polyoxyethylene ether, triisopropanolamine, 1-amino-2-methyl-2-propanol, acetone and water are stirred for 30-40 minutes to obtain the accelerator.
[0016] Preferably, the sand and gravel have a particle size range of 0.1-1 mm and a SiO2 content greater than 95%.
[0017] Preferably, the fly ash is Class II fly ash, the loss on ignition of the silicate cement is 3-3.3%, and the loss on ignition of the sulphoaluminate cement is 10-10.50%.
[0018] In a second aspect, the present application provides a method for preparing low-carbon high-performance concrete, which adopts the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned low-carbon high-performance concrete, comprising the following steps: S101. Mix silicate cement, sulphoaluminate cement, activated coal gangue powder, fly ash, sand and gravel, modified basalt fiber, limestone powder, light-burned magnesium oxide, accelerator, modified polycarboxylate water reducer and water in proportions by mass to obtain a low-carbon high-performance concrete slurry; S102, mold, shape and demould the low-carbon high-performance concrete slurry, and continue to cure to obtain low-carbon high-performance concrete.
[0019] In summary, the beneficial technical effects of this application are: 1. Enhanced mechanical properties: By using modified basalt fiber and activated coal gangue powder, the compressive strength and crack resistance of concrete have been significantly improved. Modified basalt fiber can produce tensile stress at high temperature to resist the phenomenon of thermal expansion of concrete, thereby maintaining the thermal stability of concrete volume. At the same time, the use of activated coal gangue powder not only improves the strength of concrete, but also reduces the amount of cement due to its volcanic ash activity, further reducing carbon emissions.
[0020] 2. Improved workability: The addition of modified polycarboxylate water-reducing agent makes the concrete have better slump, expansion and setting time, which helps to improve the plasticity and workability of concrete, making it more suitable for the construction of complex shapes and dense steel structures.
[0021] 3. Improved durability: The addition of sulphoaluminate cement, through its high-temperature solid-phase sintering products, such as anhydrous calcium sulphoaluminate and dicalcium silicate, quickly generates calcium sulfoaluminite and aluminum hydroxide when in contact with water, forming a dense cement stone skeleton, which improves the early strength and durability of concrete.
[0022] 4. Environmental benefits: The concrete of this application significantly reduces carbon emissions by reducing the amount of cement, utilizing industrial waste such as coal gangue powder and fly ash, and using environmentally friendly accelerators and water reducers, meeting the current high requirements for the environmental friendliness of building materials.
[0023] 5. Economic benefits: The use of low-cost raw materials and simple production process make this low-carbon high-performance concrete have a high cost-effectiveness and is suitable for large-scale promotion and application, especially in the fields of infrastructure construction and civil construction. DETAILED DESCRIPTION
[0024] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased from the market. The coal gangue includes the following components in mass percentage: Al2O3 49.36%, SiO2 43.68%, CaO 1.47%, TiO2 1.23%, SO3 1.21%, Fe2O3 0.66%, K2O 0.57%, MgO 0.49%, and other oxides 1.33%; the loss on ignition of coal gangue is 25.69%; the silicate cement includes the following components in mass percentage: Al2O3 9.81%, SiO2 24.04%, CaO 50.78%, TiO2 0.24%, SO3 2.88%, Fe2O3 6.33%, K2O 0.82%, MgO 2.85%, other oxides 2.25%; the loss on ignition of silicate cement is 3.15%; sulphoaluminate cement includes the following components in mass percentage: Al2O3 18.44%, SiO2 11.85%, CaO 47.37%, TiO2 0.45%, SO314.93%, Fe2O3 1.41%, Na2O1.98%, MgO 1.36%, other oxides 2.21%; the loss on ignition of sulphoaluminate cement is 10.25%; the particle size range of sand and gravel is 0.1-1mm, and the SiO2 content is greater than 95%; the fly ash is Class II fly ash.
[0025] In the following examples, preparation examples and comparative preparation examples, 1 part means 1 kg.
[0026] Preparation Example 1 Preparation of activated coal gangue powder The preparation method of activated coal gangue powder is as follows: firstly, blocky coal gangue is crushed into particles with a particle size of 6-10 mm by a jaw crusher, the crushed coal gangue particles are put into a ball mill, a steel ball with a diameter of 20 mm and a ball-to-material ratio of 4:1 are used, and the coal gangue powder is obtained by ball milling for 120 minutes at a speed of 100 r / min, and the coal gangue powder is sieved through a 150-mesh sieve to obtain ball-milled activated coal gangue powder; the ball-milled activated coal gangue powder is then put into a high-temperature furnace at 750°C, kept warm for 45 minutes for thermal activation, and after the thermal activation is completed, the coal gangue powder is immediately taken out from the high-temperature furnace and naturally cooled to room temperature at room temperature to obtain activated coal gangue powder.
[0027] Preparation Example 2 Preparation of modified basalt fiber The preparation method of modified basalt fiber comprises the following steps: S31. According to the mass fraction, 10 parts of basalt fiber and 7 parts of spodumene were put into a ball mill and ground for 6 hours, then heated to 260°C at a rate of 4°C / min, kept warm for 9 hours, then heated to 460°C at a rate of 5°C / min and kept warm for 8 hours, and finally heated to 670°C at a rate of 6°C / min and kept warm for 2 hours, and then cooled in the furnace to obtain a mixed powder; S32. According to the mass proportions, 10 parts of the mixed powder are uniformly mixed with 12 parts of high-rubber powder, 12 parts of calcium carbonate powder, 6 parts of maleic anhydride grafted polypropylene (grafting rate is 1%) and 4 parts of titanium dioxide. Under the protection of nitrogen atmosphere, the mixture is heated to 1700°C for melt blending for 1.6 hours. Then, a twin-screw extruder is used to extrude the roving at a speed of 150 rpm / min. The roving is then connected to a wire drawing machine. The temperature in the wire drawing machine is controlled to 750°C and the speed of the wire drawing machine is controlled to 300 m / min to obtain filaments with a diameter of 10-20 μm. Finally, the filaments are cut into a length of 15 mm by a cutting machine to obtain modified basalt fibers.
[0028] Preparation Example 3 Preparation of modified polycarboxylate water reducer The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps: S51. Add 18 mol of acrylic acid and 1 mol of methyltrimethoxysilane to 5 kg of water, stir evenly, and obtain a mixed solution A; S52. Add 0.3 mol of vitamin C and 0.8 mol of 3-mercaptopropionic acid to 2 kg of water, stir evenly, and obtain a mixed solution B; S53. Add 1 mol of benzoic anhydride-modified methyl allyl polyoxyethylene ether and 7 mol of isopentanol polyoxyethylene ether to 23 kg of water and stir, then add 1 mol of hydrogen peroxide, stir and heat to 47°C, then add dropwise the mixed solution A and the mixed solution B at the same time, after the addition is completed for 3 hours, continue stirring and react for 3 hours, then add NaOH aqueous solution to adjust the pH value to 6.8, and obtain a modified polycarboxylic acid water reducer.
[0029] Preparation Example 4 Preparation of accelerator The accelerator comprises the following raw materials, calculated by weight: 100 parts of hydroxyethyl acrylate, 0.2 parts of diisopropylbenzene peroxide, 9 parts of bis(allyl alcohol)-terminated polyoxyethylene ether, 5 parts of triisopropylamine, 4 parts of 1-amino-2-methyl-2-propanol, 110 parts of acetone, and 100 parts of water. The preparation method of the accelerator is as follows: according to the weight parts, hydroxyethyl acrylate, diisopropylbenzene peroxide, bis(allyl alcohol)-terminated polyoxyethylene ether, triisopropylamine, 1-amino-2-methyl-2-propanol, acetone and water are stirred for 35 minutes to obtain the accelerator.
[0030] Preparation Comparative Example 1 The same as Preparation Example 4, except that: 18 parts of bisallyl alcohol-terminated polyoxyethylene ether, 0 parts of triisopropanolamine, and 0 parts of 1-amino-2-methyl-2-propanol.
[0031] Preparation Comparative Example 2 The same as Preparation Example 4, except that: 0 parts of bisallyl alcohol-terminated polyoxyethylene ether, 18 parts of triisopropanolamine, and 0 parts of 1-amino-2-methyl-2-propanol.
[0032] Preparation Comparative Example 3 The same as Preparation Example 4, except that: 0 parts of bisallyl alcohol-terminated polyoxyethylene ether, 0 parts of triisopropanolamine, and 18 parts of 1-amino-2-methyl-2-propanol.
[0033] Example 1 A low-carbon high-performance concrete comprises the following raw materials, measured by weight: 150 parts of silicate cement, 24 parts of sulphoaluminate cement, 120 parts of activated coal gangue powder, 60 parts of fly ash, 600 parts of sand and gravel, 60 parts of modified basalt fiber, 20 parts of limestone powder, 10 parts of light-burned magnesium oxide, 2 parts of accelerator, 7 parts of modified polycarboxylate water reducer, and 180 parts of water, wherein the accelerator is prepared as in Preparation Example 4.
[0034] The above-mentioned method for preparing low-carbon high-performance concrete comprises the following steps: S101. Mix silicate cement, sulphoaluminate cement, activated coal gangue powder, fly ash, sand and gravel, modified basalt fiber, limestone powder, light-burned magnesium oxide, accelerator, modified polycarboxylate water reducer and water in proportions by mass to obtain a low-carbon high-performance concrete slurry; S102, mold, shape and demould the low-carbon high-performance concrete slurry, and continue to cure to obtain low-carbon high-performance concrete.
[0035] Example 2 A low-carbon high-performance concrete comprises the following raw materials, measured by weight: 180 parts of silicate cement, 27 parts of sulphoaluminate cement, 150 parts of activated coal gangue powder, 80 parts of fly ash, 700 parts of sand and gravel, 65 parts of modified basalt fiber, 25 parts of limestone powder, 12 parts of light-burned magnesium oxide, 3 parts of accelerator, 10 parts of modified polycarboxylate water reducer, and 220 parts of water, wherein the accelerator is prepared in Preparation Example 4.
[0036] The above-mentioned method for preparing low-carbon high-performance concrete comprises the following steps: S101. Mix silicate cement, sulphoaluminate cement, activated coal gangue powder, fly ash, sand and gravel, modified basalt fiber, limestone powder, light-burned magnesium oxide, accelerator, modified polycarboxylate water reducer and water in proportions by mass to obtain a low-carbon high-performance concrete slurry; S102, mold, shape and demould the low-carbon high-performance concrete slurry, and continue to cure to obtain low-carbon high-performance concrete.
[0037] Example 3 A low-carbon high-performance concrete comprises the following raw materials, measured by weight: 170 parts of silicate cement, 26 parts of sulphoaluminate cement, 140 parts of activated coal gangue powder, 70 parts of fly ash, 650 parts of sand and gravel, 63 parts of modified basalt fiber, 22 parts of limestone powder, 11 parts of light-burned magnesium oxide, 2.4 parts of accelerator, 8 parts of modified polycarboxylate water reducer, and 200 parts of water, wherein the accelerator is prepared in Preparation Example 4.
[0038] The above-mentioned method for preparing low-carbon high-performance concrete comprises the following steps: S101. Mix silicate cement, sulphoaluminate cement, activated coal gangue powder, fly ash, sand and gravel, modified basalt fiber, limestone powder, light-burned magnesium oxide, accelerator, modified polycarboxylate water reducer and water in proportions by mass to obtain a low-carbon high-performance concrete slurry; S102, mold, shape and demould the low-carbon high-performance concrete slurry, and continue to cure to obtain low-carbon high-performance concrete.
[0039] Comparative Example 1 The same as Example 3, except that an equal amount of unmodified basalt fibers with a diameter of 10-20 μm and a length of 15 mm are used instead of the modified basalt fibers.
[0040] Comparative Example 2 The same as Example 3, except that an equal amount of polyhydroxy acid-based high-efficiency water reducer (water reduction rate of 30%) is used instead of the modified polycarboxylic acid water reducer.
[0041] Comparative Example 3 The same as Example 3, except that the accelerator is prepared in Comparative Example 1.
[0042] Comparative Example 4 The same as Example 3, except that the accelerator is prepared in Comparative Example 2.
[0043] Comparative Example 5 The same as Example 3, except that the accelerator is prepared in Comparative Example 3.
[0044] Comparative Example 6 The same as Example 3, except that: 310 parts of Portland cement, 26 parts of sulphoaluminate cement, and 0 parts of activated coal gangue powder.
[0045] Performance Testing The low-carbon high-performance concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 6 was made into test pieces. The test pieces were cubes with a side length of 150 mm. The surfaces were sealed with a polyethylene film and cured at room temperature for 24 hours before demolding. The concrete was moved to a standard curing box and cured to the corresponding age. The following tests were performed. The test results are shown in Table 1.
[0046] Compressive strength: After 28 days of curing, the test shall be carried out in accordance with the relevant provisions of GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete"; The crack resistance of concrete shall be tested after 28 days of curing in accordance with the relevant provisions of GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete"; The setting time is tested in accordance with the relevant provisions of GB / T1346-2011 "Test methods for water consumption, setting time and stability of cement standard consistency"; The slump and expansion are tested in accordance with GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures"; carbon emission estimates refer to the "Building Carbon Emission Calculation Standard" (GB / T 51366-2019) and "Green and Low-Carbon Manufacturing Technology for Cement and Concrete".
[0047] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The low-carbon, high-performance concrete prepared in Examples 1 to 3 has good compressive strength, slump, expansion, setting time, crack resistance and durability, etc. In addition, it also has significant economic and environmental benefits, greatly reduces carbon emissions, and is suitable for large-scale promotion and application.
[0048] 2) The comparative analysis of the performance of the low-carbon high-performance concrete prepared in Example 3 and Comparative Example 1 shows that the preparation method of the modified basalt fiber effectively improves the performance of the fiber through a series of physical and chemical treatments, enabling it to play a key role in low-carbon high-performance concrete, not only improving the crack resistance of the concrete, but also enhancing the overall performance and durability of the concrete through its synergistic effect with other components.
[0049] 3) The performance comparison analysis of the low-carbon high-performance concrete prepared in Example 3 and Comparative Example 2 shows that the modified polycarboxylate water-reducing agent effectively improves the pore structure of concrete and enhances the compressive strength and crack resistance of concrete through its steric hindrance effect and dispersion performance. Working together with activated coal gangue powder, sulphoaluminate cement and other components, the modified polycarboxylate water-reducing agent not only improves the workability of concrete, but also promotes the early and long-term strength development of concrete, while reducing cement consumption and reducing carbon emissions.
[0050] 4) The performance comparison analysis of the low-carbon high-performance concrete prepared in combination with Example 3 and Comparative Examples 3-5 shows that the preparation method of the accelerator involves the mixing and reaction of multiple components, which work together to form an accelerator with specific functions, which plays a key role in concrete. Synergistic effect between bis-allyl alcohol-terminated polyoxyethylene ether, triisopropanolamine, and 1-amino-2-methyl-2-propanol: These components interact in the polymerization reaction to form a polymer network with specific structure and performance. As a cross-linking agent, bis-allyl alcohol-terminated polyoxyethylene ether reacts with hydroxyethyl acrylate to form a network structure; triisopropanolamine, as a catalyst, accelerates this process; and 1-amino-2-methyl-2-propanol improves the early strength of concrete through the carbonization reaction of its amino group. The joint action of these components not only improves the early strength of concrete, but also improves its crack resistance and durability. The accelerator effectively reduces the amount of cement in concrete through the interaction of the above components, while improving the strength, crack resistance and durability of concrete materials. The addition of this accelerator enables low-carbon high-performance concrete to achieve higher early strength and better environmental adaptability while maintaining good workability, providing strong support for the large-scale application of concrete.
[0051] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A low-carbon high-performance concrete, characterized in that: The preparation raw materials include the following by weight: 150-180 parts of silicate cement, 24-27 parts of sulphoaluminate cement, 120-150 parts of activated coal gangue powder, 60-80 parts of fly ash, 600-700 parts of sand and gravel, 60-65 parts of modified basalt fiber, 20-25 parts of limestone powder, 10-12 parts of light-burned magnesium oxide, 2-3 parts of accelerator, 7-10 parts of modified polycarboxylic acid water reducer and 180-220 parts of water.
2. A low-carbon high-performance concrete according to claim 1, characterized in that: The preparation method of the activated coal gangue powder comprises the following steps: firstly crushing blocky coal gangue into particles with a particle size of 6-10 mm by using a jaw crusher, placing the crushed coal gangue particles into a ball mill, using a steel ball with a diameter of 20 mm and a ball-to-material ratio of 4:1, ball milling for 120 minutes at a rotation speed of 100 r / min to obtain coal gangue powder, sieving the coal gangue powder through a 150-mesh sieve to obtain ball-milled activated coal gangue powder; and then placing the ball-milled activated coal gangue powder into a high-temperature furnace at 750° C., keeping the temperature for 45 minutes for thermal activation, and immediately taking the coal gangue powder out of the high-temperature furnace after the thermal activation is completed, and naturally cooling it to room temperature at room temperature to obtain activated coal gangue powder.
3. A low-carbon high-performance concrete according to claim 1, characterized in that: The preparation method of the modified basalt fiber comprises the following steps: S31. According to the mass fraction, 10 parts of basalt fiber and 7 parts of spodumene were put into a ball mill and ground for 5-6 hours, then heated to 260°C at a rate of 4°C / min, kept warm for 9 hours, then heated to 460°C at a rate of 5°C / min and kept warm for 8 hours, and finally heated to 670°C at a rate of 6°C / min and kept warm for 2 hours, and then cooled in the furnace to obtain a mixed powder; S32. According to the mass proportions, 10 parts of the mixed powder were mixed evenly with 12 parts of high-rubber powder, 12 parts of calcium carbonate powder, 6 parts of compatibilizer and 4 parts of titanium dioxide. Under the protection of nitrogen atmosphere, the mixture was heated to 1700°C for melt blending for 1.6 hours. Then, a twin-screw extruder was used to extrude the roving at a speed of 150 rpm / min. The roving was then connected to a wire drawing machine. The temperature in the wire drawing machine was controlled at 750°C and the speed of the wire drawing machine was controlled at 300 m / min to obtain filaments with a diameter of 10-20 μm. Finally, the filaments were cut into a length of 15 mm by a cutting machine to obtain modified basalt fibers.
4. A low-carbon high-performance concrete according to claim 3, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene, and the grafting rate is 1%.
5. The low-carbon high-performance concrete according to claim 1, characterized in that: The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps: S51, adding 18 mol of acrylic acid and 1 mol of methyltrimethoxysilane to 5 kg of water, stirring evenly, to obtain a mixed solution A; S52, adding 0.3 mol of vitamin C and 0.8 mol of 3-mercaptopropionic acid to 2 kg of water, stirring evenly, to obtain a mixed solution B; S53. Add 1 mol of benzoic anhydride modified methyl allyl polyoxyethylene ether and 7 mol of isopentanol polyoxyethylene ether to 23 kg of water and stir, then add 1 mol of hydrogen peroxide, stir and heat to 47°C, then drop mixed solution A and mixed solution B at the same time. After the addition is completed for 3 hours, continue stirring and react for 3 hours, then add NaOH aqueous solution to adjust the pH value to 6.8, and obtain a modified polycarboxylic acid water reducer.
6. The low-carbon high-performance concrete according to claim 1, characterized in that: The accelerator includes the following raw materials, calculated by weight: 100 parts of hydroxyethyl acrylate, 0.2 parts of dicumyl peroxide, 9 parts of bis(allyl alcohol)-terminated polyoxyethylene ether, 5 parts of triisopropanolamine, 4 parts of 1-amino-2-methyl-2-propanol, 110 parts of acetone, and 100 parts of water.
7. A low-carbon high-performance concrete according to claim 6, characterized in that: The preparation method of the accelerator is as follows: according to the mass fractions, hydroxyethyl acrylate, diisopropylbenzene peroxide, bis(allyl alcohol)-terminated polyoxyethylene ether, triisopropanolamine, 1-amino-2-methyl-2-propanol, acetone and water are stirred for 30-40 minutes to obtain the accelerator.
8. The low-carbon high-performance concrete according to claim 1, characterized in that: The particle size of the sand and gravel is in the range of 0.1-1 mm, and the SiO2 content is greater than 95%.
9. The low-carbon high-performance concrete according to claim 1, characterized in that: The fly ash is Class II fly ash, the loss on ignition of the silicate cement is 3-3.3%, and the loss on ignition of the sulphoaluminate cement is 10-10.50%.
10. A method for preparing a low-carbon high-performance concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S101. Mix silicate cement, sulphoaluminate cement, activated coal gangue powder, fly ash, sand and gravel, modified basalt fiber, limestone powder, light-burned magnesium oxide, accelerator, modified polycarboxylate water reducer and water in proportions by mass to obtain a low-carbon high-performance concrete slurry; S102, mold the low-carbon high-performance concrete slurry, shape it and demould it, and continue to cure it to obtain low-carbon high-performance concrete.
Citation Information
Cited By
High-performance low-carbon concrete composite admixture and preparation method thereof
CN119977478A
Coal-based multi-element solid waste artificial lightweight aggregate as well as preparation method and application thereof
CN120383465A
Coal-based multi-element solid waste artificial light aggregate, preparation method and application thereof
CN120383465B